2020
DOI: 10.1155/2020/8965459
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology-Based and Clinically Relevant Prediction of the Potential Targets of Chinese Herbs in Ovarian Cancer Patients

Abstract: Reports increasingly suggest that Chinese herbal medicine (CHM) has been used to treat ovarian cancer (OvCa) with a good curative effect; however, the molecular mechanisms underlying CHM are still unclear. In this retrospective study, we explored CHM’s molecular targets for the treatment of OvCa based on clinical data and network pharmacology. We used the Kaplan-Meier method and Cox regression analysis to verify the survival rate of 202 patients with CHM-treated OvCa. The association between CHM and survival t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…In recent years, Chinese medicine adjuvant therapy has been widely used in the clinical treatment of ovarian cancer. By regulating the immune function of the body, it can improve the toxic and side effects caused by chemotherapy, thus inhibiting the metastasis and recurrence of cancer cells, improving the clinical efficacy, and prolonging the survival time [ 6 , 7 ]. Clinical experience has shown that most patients with ovarian cancer will have different degrees of psychological problems, such as anxiety, anger, depression, giving up, and other psychological changes, so it is very necessary to implement appropriate psychological care interventions for patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Chinese medicine adjuvant therapy has been widely used in the clinical treatment of ovarian cancer. By regulating the immune function of the body, it can improve the toxic and side effects caused by chemotherapy, thus inhibiting the metastasis and recurrence of cancer cells, improving the clinical efficacy, and prolonging the survival time [ 6 , 7 ]. Clinical experience has shown that most patients with ovarian cancer will have different degrees of psychological problems, such as anxiety, anger, depression, giving up, and other psychological changes, so it is very necessary to implement appropriate psychological care interventions for patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Ge et al (10) provided a comprehensive meta-analysis for people with OC, but they only investigated the efficacy of TCM concerning survival, QOL, and immune function without assessing its safety. Coincidentally, network pharmacology conducted by Sun et al (25) also paid attention to the potential targets of TCM for OC patients. However, in our study, which included 11 RCTs consisting of 863 GC patients, it was shown that TCM plus chemotherapy can provide more durable disease control and improve GC patients' QOL without substantially increasing AEs compared with chemotherapy alone, and the major ingredients and major targets involved in the effective treatments were also illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…This compound is a compound of organic acid that was isolated for the first time from Ginkgo biloba L. (Feng-Yung et al, 1962; D. Zhou et al, 2012). According to Sun et al (2020), this compound is a potential source of anticancer drugs for ovarian cancer. This compound also has the potential as a therapeutic agent for improving asthma (Clyne et al, 2020).…”
Section: Figure 1 Gas Chromatogram Of Bouea Macrophylla Fruit Juicementioning
confidence: 99%